Non-Invasive Measurement of the Temperature Using Scanning Small Coils - AMANO, MORIKAZU; HASEGAWA, TAKEO; ONO, HIROBUMI; YAMAMOTO, ITSUO; MAEDA, KAYOKO; ANDO, SATOSHI; SUZUKI, TOMOAKI; TAKAHASHI, TOHRU; MONZEN, HAJIME; FUKUYAMA, ATSUSHI (Japanese Journal of Hyperthermic Oncology, 2004)
The temperature measurement of tumor is very important for hyperthermia. A temperature is measured by inserting a thermocouple thermometer into a living body. The fault of this method is that it can get only partial temperature and it has large invasive to the patient. Therefore, it method can't know even if a part of temperature rises. We researched the matter whether temperature measurement could be done without stabbing a thermometer by using the small coils. A magnetic field is generated when the radio-frequency is charged with electricity of the high frequency to the objects. Magnetic field is caught with the coil which put this magnetic field on making it stand opposite to each other. The electric fields decrease by 1/ (2πr). Then, we can calculate the profile of the electric fields using this equation. There are strong correlation between the radio frequency current and temperature in this object. Therefore, we can estimate the temperature distribution in the heating object non-invasive. The results of this study confirmed, there was strong correlation between temperature distribution using thermography and distribution of RF currents from our methods.